Community and Family-Centered Midwifery Care for Moderate Anemia in Third Trimester: The Case of Mrs. 'I' in Pemangket (Journal of Social And Education Research, 2025)
Anemia during pregnancy remains a major health issue, especially in developing countries like Indonesia. This report presents community midwifery care for the family of Mr. “M,” focusing on Mrs. “I” who was diagnosed with moderate anemia in the third trimester of pregnancy in Pemangket Hamlet, Ubung Village, Jonggat District, Central Lombok Regency. The objective of this activity was to provide education and intervention related to pregnancy anemia using a family-based approach. The method used is a case study with steps including problem identification, analysis, potential diagnosis, planning, intervention, and evaluation. The assessment showed that lack of compliance in taking iron tablets and limited nutritional knowledge were the main contributing factors to anemia. Interventions such as health education, iron tablet monitoring, and family support led to increased awareness and adherence in managing anemia. This community-based approach is expected to serve as an effective strategy in tackling pregnancy-related anemia in rural areas.